2008
DOI: 10.1088/1367-2630/10/7/073020
|View full text |Cite
|
Sign up to set email alerts
|

The non-equilibrium nature of culinary evolution

Abstract: Food is an essential part of civilization, with a scope that ranges from the biological to the economic and cultural levels. Here we study the statistics of ingredients and recipes taken from Brazilian, British, French, and Medieval cookbooks. We find universal distributions with scale invariant behavior. We propose a copy-mutate process to model culinary evolution that fits very well our empirical data. We find a cultural "founder effect" produced by the nonequilibrium dynamics of the model. Both the invarian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 22 publications
1
40
2
2
Order By: Relevance
“…We build an evolution model of Chinese cuisines based on the simple notion that geographical proximity breeds more communication and migration. Our model uses the copy-and-mutate model of recipe evolution [16]. We tested two models that use topological distance and physical distance respectively, and found that the model using topological distance produces better results.…”
Section: Model and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…We build an evolution model of Chinese cuisines based on the simple notion that geographical proximity breeds more communication and migration. Our model uses the copy-and-mutate model of recipe evolution [16]. We tested two models that use topological distance and physical distance respectively, and found that the model using topological distance produces better results.…”
Section: Model and Validationmentioning
confidence: 99%
“…Each ingredient i has a fitness value f i , randomly drawn from a uniformly distribution in [0, 1]. This fitness represents intrinsic properties such as nutritional value, flavor, cost, and availability [16]. All the symbols used in our model are listed in Table 2.…”
Section: Model and Validationmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73][74][75][76]) is premised, at least in part, on the notion that one can make recommendations for novel, but purportedly successful, flavour pairings based on the identification of common flavour compounds (see Fig. 4).…”
Section: The Computational Gastronomy Approach To Pairing Flavoursmentioning
confidence: 99%
“…With the rapid economic expansion and migration from rural to urban areas, many individuals have adopted Western lifestyle habits (Ford & Mokdad, 2008). The rescue of regional culinary value and its adaptation to the contemporaneous reality make it possible to increase the demand of accessible and known products to the population and, with the appropriate dietary modifications, provide a healthier daily cuisine (Coitinho, Monteiro, & Popkin, 2002;Kinouchi, Diez-Garcia, Holanda, Zambianchi, & Roque, 2008). 232 V. C. Ginani et al Considering these facts, it is necessary to study techniques and procedures for the production/preparation of meals that fulfill the healthful requirements established by the World Health Organization/Food and Agriculture Organization (WHO/FAO, 2003) concerning the ingestion of fat without ignoring the sensorial satisfaction of the consumer (Jones, 2005).…”
Section: Introductionmentioning
confidence: 99%